Effect of Zinc Sulfate and Adjuvants on the Physicochemical Properties and Efficacy of Bromoxynil with Terbythylazine and Nicosulfuron Mixtures Against Echinochloa crus-galli L. - Robert Idziak; Violetta Szuba-Adamska; Hubert Waligóra; Piotr Szulc (Agriculture)
The study aimed to evaluate the effects of methyl esters adjuvant, pH reducer, and zinc sulfate on the physicochemical properties (contact angle, surface tension) of a spray liquid and a bromoxynil + terbuthylazine + nicosulfuron mixture’s efficacy. Cockspur (Echinochloa crus-galli L.) was used as the test plant. The placement of any adjuvant in the spray liquid affected the reduction in contact angle, with zinc sulfate reducing it from 75.9 to 66.3°, methyl esters adjuvant from 61.8 to 47.1°, pH reducer from 58.3 to 47.0°, zinc sulfate + methyl esters adjuvant from 64.9 to 58.4°, and zinc sulfate + pH reducer from 57.1 to 44.6°. A decrease in contact angle was found with a reduction in herbicide doses, from 65.6 to 59.0°. The highest pH of the spray liquid with herbicides was found when the methyl esters adjuvant was added to the liquid (6.82–7.17), followed by 6.43–6.80 when zinc sulfate was added, and 6.05–6.30 for zinc sulfate with methyl esters adjuvant. The inclusion of adjuvant pH reducer very strongly reduced the liquid reaction to 3.28–3.60, and it was reduced to 2.76–2.90 in the presence of zinc sulfate. Bromoxynil + terbuthylazine + nicosulfuron mixtures applied with methyl esters adjuvant and zinc sulfate with pH reducer showed the highest efficacy (85–98% and 82–96%), and the efficacy was 64–81% when methyl esters adjuvant with zinc sulfate were used. The effect of the herbicide mixture with only zinc sulfate was noticeably weaker (40–81%), and it was very weak (13–43%) in the presence of adjuvant pH reducer only. On the basis of the ED50 values, the most favorable mixtures were those containing methyl esters adjuvant, methyl esters adjuvant + zinc sulfate and pH reducer + zinc sulfate in addition to the herbicides. Research has indicated that zinc sulfate could be used as an adjuvant, and will support not only the action of herbicides, but also the development of maize plants.